Energy criterion to select the behavior of dynamical masses in technicolor models - Doff, A. [UNESP]; Natale, A. A. [UNESP] (Elsevier, 2002)
We propose a quite general ansatz for the dynamical mass in technicolor models. We impose on this ansatz the condition that it should lead to the deepest minimum of energy. This criterion selects a particular form of the technifermion self energy. © 2002 Elsevier Science B.V. All rights reserved.
Keywords: analytic method; dynamics; model; phenomenology; standard; theory